Evaluation of anti‐acne property of purified bee venom serum in humans. (24th May 2016) - Han, Sang Mi; Pak, Sok Cheon; Nicholls, Young Mee; Macfarlane, Nicola
Summary: Objective: Acne vulgaris is a chronic dermatologic disease with four factors involved in the development of lesions. Treatments need to address as many of these underlying factors as possible in order to reduce acne lesions. As such, purified bee venom (PBV ™ ) serum is an attractive therapeutic option for acne, but little data exist on the efficacy of this treatment strategy. Methods: In this prospective, noncomparative study, 30 subjects having mild‐to‐moderate acne vulgaris were enrolled and treated with PBV ™ serum twice daily for a period of 6 weeks. Clinical evaluation of lesions by expert visual grading and image analysis were made at weeks 0 (baseline), 3, and 6. Results: The average visual acne grade of all volunteers significantly improved with the PBV ™ serum treatment at weeks 3 ( P < 0.05) and 6 ( P < 0.001) when compared with the baseline grade at week 0. In addition, there was a mean percent improvement of 8.6% and 52.3% in acne grade observed after 3 and 6 weeks of PBV ™ serum use, with 20% and 77% of the subjects showing improvement, respectively, when compared with baseline. Moreover, the subjects showed improvement in open comedones, closed comedones, papules, pustules, and nodules after 3 and 6 weeks of PBV ™ serum use. Conclusion: Six weeks of treatment with PBV ™ serum was found to be effective in the treatment of mild‐to‐moderate acne vulgaris, with no incidence of serious side effects or irritation.